2020
DOI: 10.2147/dmso.s232279
|View full text |Cite
|
Sign up to set email alerts
|

<p>DHA Protects Against Hepatic Steatosis by Activating Sirt1 in a High Fat Diet-Induced Nonalcoholic Fatty Liver Disease Mouse Model</p>

Abstract: Docosahexaenoic acid (DHA; C22; n-3) shows beneficial effects on Non-alcoholic fatty liver disease (NAFLD). Deacetylase Sirtuin1 (Sirt1) was reported to increase energy metabolism and decrease lipogenesis. Here, we investigated whether DHA plays a role in protecting against hepatic steatosis via Sirt1. Main Methods: Both in vivo and in vitro hepatic steatosis models were used: diet-induced obesity (DIO) model (middle-aged C57BL/6 mice fed a high-fat diet (HFD)) and palmitic acid (PA)-induced lipid accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
(41 reference statements)
1
7
0
Order By: Relevance
“…Apart from the aforementioned mechanisms enhanced activation of mitochondrial biogenesis has been also discussed to be associated with prevention of NAFLD 41 . Recent studies demonstrated that hepatic PGC1α-overexpression, which was also found in our INT-offspring at P21, results in increased hepatic fatty acid oxidation and reduced triacylglycerol accumulation and presumably protects against the development of hepatic steatosis 12 , 42 44 . Even though Tfam mRNA-expression did not differ between CO- and INT-offspring at P21, the observed Pgc1α upregulation, the activation of KEGG—pathway “oxidative phosphorylation” and the fact that Pgc1α methylation due to exercise were also observed in other organs prompted us to perform methylation analysis of the Pgc1α promoter region at P21.…”
Section: Discussionsupporting
confidence: 70%
“…Apart from the aforementioned mechanisms enhanced activation of mitochondrial biogenesis has been also discussed to be associated with prevention of NAFLD 41 . Recent studies demonstrated that hepatic PGC1α-overexpression, which was also found in our INT-offspring at P21, results in increased hepatic fatty acid oxidation and reduced triacylglycerol accumulation and presumably protects against the development of hepatic steatosis 12 , 42 44 . Even though Tfam mRNA-expression did not differ between CO- and INT-offspring at P21, the observed Pgc1α upregulation, the activation of KEGG—pathway “oxidative phosphorylation” and the fact that Pgc1α methylation due to exercise were also observed in other organs prompted us to perform methylation analysis of the Pgc1α promoter region at P21.…”
Section: Discussionsupporting
confidence: 70%
“…It has been shown that DHA supplementation in parallel with high-calorie feeding protects against the development of obesity-associated liver steatosis [ 34 , 35 ]. Therefore, in order to further investigate the beneficial effects of maternal DHA supplementation, we assessed the accumulation of triglycerides and cholesterol in liver samples from our four experimental groups.…”
Section: Resultsmentioning
confidence: 99%
“…A high-energy diet will not only cause a large amount of fat accumulation, resulting in an imbalance in lipid metabolism, but it will also affect the body's redox balance (Luo et al, 2020). A high-energy diet induces hyperglycemia through lipid metabolism and sugar metabolism and, subsequently, releases a large amount of free radicals, triggering oxidative stress (Park et al, 2020).…”
Section: Discussionmentioning
confidence: 99%